ChemInform Abstract: A Metal‐Free Protocol for Direct Oxidative De‐alkoxycarbonylation of Alkyl Phenyl Acetate by Molecular Iodine. Issue 37 (16th September 2014) - Humne, Vivek T.; Lokhande, Pradeep D.
Abstract The protocol is advantageous with regards to operational simplicity and good functional group tolerance.